PEMODELAN RASIONALISASI UNIT LOADER DAN HAULER TERHADAP PEMILIHAN UNIT DI PT. XYZ - Ari Nasanius; Dicky Antonius; Bantu Hotsan Simanullang (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2021)
Unit selection is important to fufill the production target of a heavy equipment contractor company. To make the right selection, it is necessary to calculate based on several parameters to determine the best investment in certain units, such as loader and hauler units. Unit rationalization is one of many way to make a standard parameter selection to reduce the number of models and brands of units. This research was conducted by analyzing the rationalization of units on loader and hauler units at PT. XYZ by calculating the data of cost per hour, physical availability, mean time between repair, cost per bank cubic meter, cost per payload and the cost of new unit to create a unit selection modeling so the modeling results are obtained to determine the unit with the best brand in each class for invested in loader and hauler units. This study succeeded in making the modeling that used for analyze the rationalization of the best units in the loader and hauler units to get the matrix of the best brand in each class that being analyzed.